(untitled) (Research, Society and Development, 2021)
The present work aims to develop and apply a didactic sequence based on the three pedagogical moments. For this, it was developed for first-year high school classes, with the theme “The Periodic Table and the Human Body”, in the first pedagogical moment, a problem situation involving the subject was taken to the students, as well as questions for surveying prior knowledge. Right after, in the second pedagogical moment of contribution of the board, video, support texts and questions, the content of the periodic table was raised, always linking to the generating theme. Finally, at the last pedagogical moment, a game similar to the super trump was used, The game called: Xenubi, had aspects related to the periodic properties in its cards. And also at this last moment, food packaging was used for students to answer extrapolation questions. The didactic sequence proved to be an important teaching tool, because following the analysis of the results, the students had an effective learning in the end. This teaching tool also promotes debate within the classroom, making students become more citizens. critics and actors in the world in which they live.